Inhalant Use among Schoolchildren in Northeast India: A Preliminary Study - Brogen Singh Akoijam; M. Nukshisangla Jamir; Ebenezer Phesao; Gojendra Singh Senjam (SAGE Publishing, 2013)
Inhalant use by children leads to poor performance in school and has been observed to precede substance use later in life. There is paucity of data on inhalant use among school children in India, particularly in the Northeast region of the country. We determined the prevalence and documented inhalant use characteristics among schoolchildren in the Northeast region of India. This cross sectional study was conducted in six states in the Northeast region of India. Schoolchildren between eighth and eleventh standards from the capital areas of the states were included in the study. Data were collected using a questionnaire. Analysis was done using descriptive statistics and Chi-square test. Of the 4074 enrolled students, data from 3943 students who responded to the inhalant use question were analyzed. Mean age was 14.8 ± 1.2 years and 51.2% of participants were male. The proportion of students who had ever used inhalants (ever user) was 18.8% and adhesive/glue was the inhalant misused by most of the students. A higher proportion of males than females were ever users ( P ≤ 0.001) and the most common place of use was at home (33.1%). Being in the presence of an older person using an inhalant or tobacco was found to be associated with use of inhalants among students. Nearly one-fifth of the students had used inhalants and nearly half used inhalants in the past month. Sensitization of the parents and school authorities to the problem, as well as preventive and curative services, should be considered.